Development of novel multifunction directly compressible co-processed excipient by melt granulation technique - Garg, Nidhi (Int J Pharm Investig, 2015)
INTRODUCTION: The objective of the present investigation was to develop a novel multifunctional directly compressible co-processed excipient consisting of dibasic calcium phosphate anhydrous, polyethylene glycol 4000 (PEG 4000) and crospovidone using Box-Behnken design. MATERIALS AND METHODS: The technique of melt granulation was adopted for the preparation of the co-processed excipient. The percentage of crospovidone (5-10% w/w), percentage of PEG 4000 (5-15% w/w) and the heating time (4-12 min) were selected as independent variables. The co-processed granules were evaluated for bulk density, tapped density, Hausner's ratio and Carr's index. Placebo tablets of co-processed granules were prepared and evaluated for hardness, friability and disintegration time. Multiple linear regression was applied to develop mathematical models for hardness, Carr' index and disintegrating time. ANOVA was applied to study the fitting and significance of the model. The optimized batches (BB) were selected for further studies. The selected batches were characterized for particle size distribution, granular friability index, moisture uptake study, differential scanning calorimetry, Fourier transform infrared spectroscopy and scanning electron microscopy. Aceclofenac was selected as model drug for the preparation of tablets. RESULTS: Aceclofenac tablets prepared using co-processed excipients showed better hardness, disintegration time and in vitro drug release as compared to aceclofenac tablets prepared using conventional wet granulation method. CONCLUSION: The developed co-processed excipient can serve as a novel co-processed excipient for improvement of tableting characteristics.